Pemanfaatan Augmented Reality dalam Pendidikan Vokasi - Hidayat, Arif; Sutopo, Yeri; Qudus, Nur (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The integration of Augmented Reality (AR) media in vocational education has emerged as a promising tool for enhancing learning experiences and aligning educational outcomes with industry demands. This study employs a qualitative approach to examine the benefits and challenges associated with the use of AR media in vocational education. Data were collected through in-depth interviews with educators, students, and education technology experts, supplemented by document analysis of curriculum frameworks and AR implementation case studies. The findings reveal several key benefits of AR in vocational education, including improved student engagement, enhanced skill acquisition through immersive simulations, and the ability to bridge the gap between theoretical knowledge and practical application. AR media also facilitates personalized learning, enabling students to progress at their own pace while fostering a deeper understanding of complex concepts. However, the study identifies significant challenges, such as high development costs, limited digital literacy among educators and students, and infrastructural constraints, particularly in resource-limited settings. Additionally, concerns regarding content standardization and the alignment of AR tools with curriculum objectives remain prevalent. The study concludes that while AR holds transformative potential for vocational education, its successful integration requires collaborative efforts among educators, policymakers, and technology providers. Recommendations include the development of cost-effective AR solutions, targeted training programs for educators, and robust policies to ensure equitable access and alignment with educational goals. This study contributes to the growing discourse on education technology, offering actionable insights for stakeholders seeking to leverage AR to enhance vocational education outcomes.